Bubaline Cholecyst Derived Extracellular Matrix for Reconstruction of Full Thickness Skin Wounds in Rats. (5th April 2016) - Shakya, Poonam; Sharma, A. K.; Kumar, Naveen; Vellachi, Remya; Mathew, Dayamon D.; Dubey, Prasoon; Singh, Kiranjeet; Shrivastava, Sonal; Shrivastava, Sameer; Maiti, S. K.; Hasan, Anwarul; Singh, K. P.
Abstract : An acellular cholecyst derived extracellular matrix (b-CEM) of bubaline origin was prepared using anionic biological detergent. Healing potential of b-CEM was compared with commercially available collagen sheet (b-CS) and open wound (C) in full thickness skin wounds in rats. Thirty-six clinically healthy adult Sprague Dawley rats of either sex were randomly divided into three equal groups. Under general anesthesia, a full thickness skin wound (20 × 20 mm 2 ) was created on the dorsum of each rat. The defect in group I was kept as open wound and was taken as control. In group II, the defect was repaired with commercially available collagen sheet (b-CS). In group III, the defect was repaired with cholecyst derived extracellular matrix of bovine origin (b-CEM). Planimetry, wound contracture, and immunological and histological observations were carried out to evaluate healing process. Significantly (P < 0.05 ) increased wound contraction was observed in b-CEM (III) as compared to control (I) and b-CS (II) on day 21. Histologically, improved epithelization, neovascularization, fibroplasia, and best arranged collagen fibers were observed in b-CEM (III) as early as on postimplantation day 21. These findings indicate that b-CEM have potential for biomedical applications for full thickness skin wound repair in rats.